Propagation of Shafira Taro (Colocasia Esculenta Var. Antiqourum) Applied TDZ, BAP, TDZ AND NAA, BAP and NAA In Vitro - Haswin, Dwi Wahyuni; Haring, Fera; Riadi, Muh; Tambung, Astina; Yanti, Nur Aida; Ilham, Ilham (Journal of Agriculture, 2025)
Shafira taro (Colocasia esculenta var. antiquorum) is a type of small-tubered taro, also known as Japanese taro, which is traded internationally. This study aims to examine the effect of various concentrations of Thidiazuron (TDZ) and Benzyl Amino Purine (BAP), as well as the combination of Thidiazuron with Naphtalene Acetic Acid (NAA) and BAP with NAA, on the multiplication of Shafira taro shoots through in vitro culture techniques. The method used in this study uses in vitro culture techniques, which are modern plant propagation science known in the world of biotechnology and allow controlled propagation and improvement of plant species. An essential component of this technique is using plant growth regulators (PGRs), critical for modulating various physiological processes in plant cells and tissues. PGRs promote growth and differentiation, optimize secondary metabolite production, and increase plant resistance. This study used a combination of main PGR treatments (TDZ, BAP, and NAA) with a total of 13 (thirteen) treatment combinations using a randomized block design, namely: k0: Control, t1: TDZ 1 ppm, t2: TDZ 2 ppm, t3: TDZ 3 ppm, b1: BAP 1 ppm, b2: BAP 2 ppm, b3: BAP 3 ppm, t1n1: TDZ 1 ppm + NAA 0.5 ppm, t2n1: TDZ 2 ppm + NAA 0.5 ppm, t3n1: TDZ 3 ppm + NAA 0.5 ppm, b1n1: BAP 1 ppm + NAA 0.5 ppm, b2n1: BAP 2 ppm + NAA 0.5 ppm, b3n1: BAP 3 ppm + NAA 0.5 ppm. Each treatment was repeated thrice, with three tissue culture bottles per repetition, resulting in 117 tubes containing one explant. The results showed that the highest number of roots, leaves, and shoots was achieved with 1 ppm BAP, while the optimal fresh weight and shoot height were obtained with 2 ppm BAP. Treatments involving combinations of TDZ, TDZ + NAA, and BAP + NAA did not produce significant results for shoot multiplication.